Factors affecting the investors' satisfaction in Industrial Zones and results in investment attraction in Industrial Zones in Binh Dinh Province, Vietnam - Hoàng Thị Hoài Hương; Nguyễn Thị Thùy Dung (My University, 2019)
Factors affecting the investors' satisfaction in Industrial Zones and results in investment attraction in Industrial Zones in Binh Dinh Province, Vietnam
Keywords: Investor satisfaction; Industrial Zones; Binh Dinh